2022
DOI: 10.3390/molecules27051607
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Venetoclax for Therapeutic Drug Monitoring in Chinese Acute Myeloid Leukemia Patients by a Validated UPLC-MS/MS Method

Abstract: Venetoclax has emerged as a breakthrough for treatment of leukemia with a wide interindividual variability in pharmacokinetics. Herein, a rapid, sensitive, and reliable UPLC-MS/MS method for quantification of venetoclax in plasma was developed and validated. The method was operated in the multiple-reaction monitoring (MRM) mode to detect venetoclax at m/z transition 868.5 > 321.0 and IS at 875.5 > 321.0, respectively. Protein precipitation prior to injection into the LC-MS/MS and the analyte was separate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Presently, research on monitoring serum Venetoclax concentration during treatment is still less. To our knowledge, there are only two methodological studies published [ 29 , 30 ], and no clinical intervention study is performed to prove the effect of serum drug concentration on treatment safety. Both the two existing studies reported that the steady-state trough concentration of Venetoclax during treatment in AML patients fluctuated in a range of 250–8000 ng/ml.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, research on monitoring serum Venetoclax concentration during treatment is still less. To our knowledge, there are only two methodological studies published [ 29 , 30 ], and no clinical intervention study is performed to prove the effect of serum drug concentration on treatment safety. Both the two existing studies reported that the steady-state trough concentration of Venetoclax during treatment in AML patients fluctuated in a range of 250–8000 ng/ml.…”
Section: Discussionmentioning
confidence: 99%
“…However, venetoclax has a high variability between patients with nonlinearity in relative bioavailability (Freise et al, 2017; Kaufman et al, 2021; Yang et al, 2022) and exhibits a severe drug–drug interaction with azole antifungals such as posaconazole (Bhatnagar et al, 2021). Therefore, it is necessary to monitor the plasma exposure of venetoclax in patients.…”
Section: Introductionmentioning
confidence: 99%
“…There are limited studies focusing on the transitivity of venetoclax to the cerebrospinal fluid (CSF), which needs to be evaluated to consider it as a treatment option for patients with central nervous system metastasis. Although an article (Yang et al, 2022) has focused on quantifying venetoclax in human plasma, there is a lack of reported analytical methods for assessing venetoclax in CSF. Therefore, we developed and validated methods using high sensitivity and specificity for determining venetoclax in human plasma and CSF using LC–MS/MS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few mass spectrometry-based methods, including liquid chromatography with tandem mass spectrometry (LC-MS/MS) have been published for the quantification of individually DCB ( Xu et al, 2012 , Liu et al, 2006 ) and VTX ( Yang et al, 2022 ) or in combination with other anti-cancer agents ( Reddy et al, 2021 , Sai Prudhvi et al, 2021 , Zhang et al, 2013 ). Bioanalytical method for determination of DCB and VTX in biological samples, have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%